2003
DOI: 10.1007/s12144-003-1018-2
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive norms as an additional predictor in the theory of planned behaviour: A meta-analysis

Abstract: This study used meta-analysis: (a) to quantify the relationship between descriptive norms and intentions, and (b) to determine the increment in variance attributable to descriptive norms after variables from the theory of planned behaviour (TPB; Ajzen, 1991) had been controlled. Literature searches revealed twenty-one hypotheses based on a total sample of N = 8097 that could be included in the review. Overall, there was a medium to strong sample-weighted average correlation between descriptive norms and intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
652
6
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 986 publications
(709 citation statements)
references
References 37 publications
44
652
6
7
Order By: Relevance
“…By comparing alternative nested models, we also found that perceived norms had a direct effect on doping behaviors. These results are slightly unexpected because in the TPB literature perceived norms are often found to be the weakest, or even non-significant, predictor of intentions [111,112]. However, unlike many non-doping related TPB studies that assessed social norms through subjective norms (i.e., perceived social approval of doping), many of the studies we analyzed assessed other aspects of social norms, such as descriptive norms (i.e., what significant others themselves do).…”
Section: Path Analysismentioning
confidence: 80%
See 2 more Smart Citations
“…By comparing alternative nested models, we also found that perceived norms had a direct effect on doping behaviors. These results are slightly unexpected because in the TPB literature perceived norms are often found to be the weakest, or even non-significant, predictor of intentions [111,112]. However, unlike many non-doping related TPB studies that assessed social norms through subjective norms (i.e., perceived social approval of doping), many of the studies we analyzed assessed other aspects of social norms, such as descriptive norms (i.e., what significant others themselves do).…”
Section: Path Analysismentioning
confidence: 80%
“…For example, it is unclear whether observing the doping behavior of others is of greater motivational importance compared to perceived social pressure from others. Finally, Rivis and Sheeran's [111] observation that young people are particularly susceptible to descriptive norms suggests that interventions with adolescent groups should be bespoke to the needs of that group in order to foster a strong sense of individuality and uniqueness.…”
Section: Path Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the words "normal" and "normalised" in the quotes below highlights the importance of descriptive norms in countering stigma to influence young people's STI testing behaviour: [7] …”
Section: Perceived Normsmentioning
confidence: 99%
“…[3][4][5][6] It is important to note that although the TPB focuses on injunctive norms -a desire to comply with the perceived wishes of others -young people are also sensitive to descriptive norms -perceptions of the behaviour of others. [3,7] There may therefore be a need to add descriptive norm measures to the TPB to increase its utility. Other variables not specified in the TPB that may be influence STI testing include an individual's sexual history and STI testing history.…”
Section: Introductionmentioning
confidence: 99%